Influence of log and stack parameters on the conversion factors for Norway Spruce wood stacks using a 3D simulation model. Issue 2 (4th May 2022) - de Miguel-Díez, Felipe; Pettenkofer, Tim; Wallor, Evelyn; Tolosana-Esteban, Eduardo; Purfürst, Thomas; Cremer, Tobias
ABSTRACT: One method for estimating the solid wood content in a stack involves using conversion factors and multiplying these by the measured gross volume. The conversion factors can vary depending on several log and stack parameters. The aim of this study was to analyze eleven parameters using a 3D simulation model based on 541 measured logs of Norway spruce. To this end, 50 data sets were created from measured logs, where the parameters of interest in this study (e.g., length, crookedness, taper …) were classified according to different ranges. After that, 64 runs of simulations were carried out. In each simulation run, 150 stacks were modeled. The simulation results were compared with previous studies and with the measurement guidelines of several countries. This analysis revealed that the parameters midpoint diameter, length, crookedness, delimbing quality and the proportion of moderately and highly crooked logs in a stack have a considerable influence on the conversion factors. Taper, proportion of butt logs in a stack and stack height have a modest effect as do the proportion of tapered and crooked logs for low and high taper and low crookedness. In contrast, ovality and the proportion of logs stacked in opposite directions have a marginal influence on the conversion factors. Based on findings from these analyses, the current measurement guidelines of different countries can now be adapted to achieve a higher degree of accuracy.